A simple Christmas : twelve stories that celebrate the true holiday spirit - Huckabee, Mike, 1955- (New York : Sentinel, 2009)
The former presidential candidate and current talk-show host shares twelve true and heartwarming stories from his past that help recall the real meaning of Christmas.
Introduction: A simple Christmas -- Patience -- Sacrifice -- Loneliness -- Family -- Traditions -- Crisis -- Hope -- Stability -- Limitations -- Transitions -- Faith -- Rewards.
Keywords: Huckabee, Mike, -- 1955-; Huckabee, Mike, -- 1955-; Christmas stories; Christmas; Governors -- Arkansas -- Biography; Presidential candidates -- United States -- Biography; Television personalities -- United States -- Biography; Governors -- Arkansas -- Biography; Television personalities -- United States -- Biography; Christmas; Arkansas -- Biography; Arkansas -- Biography